2016
DOI: 10.1373/jalm.2016.021642
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro–B-Type Natriuretic Peptide (NT-proBNP) Immunoreactivity Is Reduced After 6 Years of Storage at −70 °C

Abstract: Background Clinical trial samples may be stored frozen for prolonged periods before analysis, which can reduce the immunoreactivity of numerous analytes, particularly peptides. We sought to determine the effect of 6 years of frozen storage on serum N-terminal pro–B-type natriuretic peptide (NT-proBNP). Methods NT-proBNP was measured from serum samples taken from 99 different patients enrolled in the CanPREDDICT study after &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…After centrifugation (15 min, 4500× g ), plasma aliquots were frozen at −80 °C until analysis. Long-term stability of the study biomarkers at −80 °C have shown negligible or minimum decreases in their immunoreactivity, otherwise not affecting their clinical meaning [ 22 , 29 , 30 ]. Routine biochemical and hematological measurements were determined at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation (15 min, 4500× g ), plasma aliquots were frozen at −80 °C until analysis. Long-term stability of the study biomarkers at −80 °C have shown negligible or minimum decreases in their immunoreactivity, otherwise not affecting their clinical meaning [ 22 , 29 , 30 ]. Routine biochemical and hematological measurements were determined at baseline.…”
Section: Methodsmentioning
confidence: 99%